Arcana rising - Cole, Kresley (Cole, Kresley. Arcana chronicles, 2016)
The Emperor unleashes hell and annihilates an army, jeopardizing the future of mankind--but Circe strikes back. The epic clash between them devastates the Arcana world and nearly kills Evie, separating her from her allies. With Aric missing and no sign that Jack and Selena escaped Richter's reach, Evie turns more and more to the darkness lurking inside her. Two Arcana emerge as game changers: one who could be her salvation, the other her worst nightmare. To take on Richter, Evie must reunite with Death and mend their broken bond. But as she learns more about her role in the future--and her chilling past--will she become a monster like the Emperor? Or can Evie and her allies rise up from Richter's ashes, stronger than ever before?